Total body irradiation + fludarabine compared to busulfan + fludarabine as “reduced-toxicity conditioning” for patients with acute myeloid leukemia treated with allogeneic hematopoietic cell transplantation in first complete remission - Giebel, Sebastian; Müller, Lutz P.; Labopin, Myriam; Sobczyk-Kruszelnicka, Malgorzata; Stelljes, Matthias; Byrne, Jenny L.; Fegueux, Nathalie; Beelen, Dietrich W.; Rovira, Montserrat; Spyridonidis, Alexandros; Blaise, Didier; Bornhäuser, Martin; et al. (Bone marrow transplantation, 2021)
The optimal conditioning for patients with acute myeloid leukemia in first complete remission treated with allogeneic hematopoietic cell transplantation (allo-HCT) has not been defined so far. In this retrospective study, we compared two “reduced-toxicity” regimens: intravenous busulfan at a total dose of 9.6 mg/kg (3 days) + fludarabine (Bu3/Flu) and total body irradiation at a dose of 8 Gy + fludarabine (TBI8Gy/Flu). In the entire study cohort (n = 518), the probabilities of overall survival (OS), leukemia-free survival (LFS), relapse and non-relapse mortality (NRM) at 2 years for Bu3/Flu and TBI8Gy/Flu were 62% vs. 72.5% (p = 0.051), 59.5% vs. 65% (p = 0.15), 30% vs. 20% (p = 0.01), and 10% vs. 14% (p = 0.18), respectively. In multivariate model for patients <50 years old, TBI8Gy/Flu was associated with improved LFS (hazard ratio (HR) = 0.5, p = 0.04), OS (HR = 0.31, p = 0.004), and survival free from both graft-versus-host disease and relapse (HR = 0.55, p = 0.03), as well as tendency to reduced risk of relapse (HR = 0.53, p = 0.08). Among patients aged 50 years or older the use of TBI8Gy/Flu was associated with increased incidence of NRM (HR = 3.9, p = 0.0009), with no significant impact on other outcome measures. We conclude that the use of TBI8Gy/Flu as “reduced-toxicity” regimen may be advised in younger patients with AML referred for allo-HCT.